Influence of upper-body high-intensity intermittent training on energy metabolism and maximal oxygen uptake in elite swimmers - Zhang, L.; Li, H.; Wang, T.; Chen, C. (Frontiers in Physiology, 2025)
Purpose: This paper aimed to investigate the effects of upper-body high-intensity interval training (HIIT) on energy metabolism and maximal oxygen uptake (VO2max) in elite swimmers.